Rhodium‐Catalyzed C−H Functionalization of Indoles with Diazo Compounds: Synthesis of Structurally Diverse 2, 3‐Fused Indoles. Issue 1 (20th October 2017) - Gao, Mengying; Yang, Yaxi; Chen, Hua; Zhou, Bing
Abstract: A Rhodium‐catalyzed C2‐H functionalization of indoles with diazo compounds, followed by intramolecular nucleophilic addition to C=O or C=C bonds, is reported for divergent synthesis of 2, 3‐fused indoles. Besides acceptor/acceptor diazo compounds, donor/acceptor diazo compounds are broadly tolerated, giving various 2, 3‐fused indoles with perfect diastereocontrol. Notably, a selective C−H dialkylation reaction at C2 and C7 position of indoles has also been developed by simply changing the reaction conditions. This environmentally benign transformation proceeds under mild conditions and gives dinitrogen as the only by‐product. Abstract :